Organizational Factors that Contribute to the Spiritual Development of College Athletes: A Case Study of a Religious University. Issue 1 (April 2014) - Nite, Calvin; Singer, John N.
<x content-type="archive" xml:space="preserve">Abstract</x> Although the concept of college athlete development has received ample attention within the literature, limited attention has been paid specifically to the spiritual development of these athletes. More specifically, little attention has been paid to how organizational contexts might impact the spiritual development of athletes. Using qualitative research methods, we interviewed university and athletic department leaders (i.e., head coaches, university administrators, athletics administrators, faculty members) and analyzed relevant documents of one religiously affiliated university within the United States in efforts to glean insight into some important factors that contribute to the spiritual development among their athletes. The findings indicated that the mission and the culture of the university established a foundation and helped set the tone for how these leaders thought about and engaged in certain practices aimed at fostering the spiritual development of the athletes at the university. In particular, because the spiritual development of athletes was a major aspect of these leaders' job expectations there was a great devotion of time and monetary resources to this endeavor. Further implications of these findings and opportunities for future research are discussed.